Definition of a tool to assess shared decision‐making (SDM) on women with breast cancer: A value‐based approach. Issue 5 (13th September 2022) - Angioletti, Carmen; de Mattia, Egidio; Carloni, Luca M.; Morsella, Alisha; Fabi, Alessandra; Orlandi, Armando; Tortora, Giampaolo; de Belvis, Antonio G.
Abstract: Background and Aims: In oncology, there is increasing talk of personalized treatment and shared decision‐making (SDM), especially when multiple treatment options are available with different outcomes depending on patient preference. The present study aimed to define the set of main dimensions and relative tools to assess the Value brought to patients from a Breast Cancer's Clinical pathway structured according to a dynamic SDM framework. Methods: Starting from our previous systematic review of the literature, a deep search of the main evidence‐based and already validated questionnaires was carried out. In the second phase, to corroborate this grid, a Delphi survey was conducted to assess each questionnaire identified for each dimension, against the following seven value‐based criteria: Clinical Benefit, Safety, Care Team Well Being, Patient Reported Outcomes Measures, Green Oncology, Impact on Health Budget, and Genomic Profile. Results: The resulting 7‐dimension questionnaire is composed of 72 questions. Of these, some quantitatively and objectively assess the evolution of the patient's disease state, whereas others aim to ask patients about their active involvement in decisions affecting them and to investigate whether they were free to explore their preferences. Furthermore, to frame the analyzed phenomenon at the right time, for each questionnaire section, the specific, evidence‐based timing of administration is indicated. Conclusion: The resulting questionnaire is validated in its entirety and it is composed of a set of questions and relative time point for data collections to assess the Value brought to patients undertaking a Breast Cancer's Clinical pathway, structured according to a dynamic SDM framework. It constitutes a quantitative instrument to integrate patient centeredness with a personalized perspective in the care management of women with breast cancer.